2020
DOI: 10.1101/2020.05.20.106328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wnt16 Elicits a Protective Effect Against Fractures and Supports Bone Repair in Zebrafish

Abstract: SummaryBone homeostasis is a dynamic, multicellular process which is required throughout life to maintain bone integrity, prevent fracture and respond to skeletal damage. WNT16 has been linked to bone fragility and osteoporosis in humans, as well as functional haematopoiesis of leukocytes in vivo, but the mechanisms by which it promotes bone health and repair are not fully understood. We used CRISPR-Cas9 to generate mutant zebrafish lacking Wnt16 (wnt16-/-) to study its effect on bone dynamically. wnt16 mutant… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…In our study, phenotypes in wnt16 -/- mutant larvae were indistinguishable for three different alleles. Moreover, wnt16 -/- mutants did not exhibit loss of caudal fin rays, in agreement with a wnt16 presumptive null allele generated by McGowan et al (McGowan et al, 2021), and contrasting with the allele of Qu et al (Qu et al, 2021). The allele of Qu et al comprised a 11bp deletion in exon 3, which was generated by two gRNAs with different target sites.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In our study, phenotypes in wnt16 -/- mutant larvae were indistinguishable for three different alleles. Moreover, wnt16 -/- mutants did not exhibit loss of caudal fin rays, in agreement with a wnt16 presumptive null allele generated by McGowan et al (McGowan et al, 2021), and contrasting with the allele of Qu et al (Qu et al, 2021). The allele of Qu et al comprised a 11bp deletion in exon 3, which was generated by two gRNAs with different target sites.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have reported disparate skeletal phenotypes in zebrafish homozygous for presumptive wnt16 null alleles; for example, Qu et al reported loss of caudal fin rays, whereas caudal fin rays in mutants described by McGowan et al are intact (McGowan et al, 2021; Qu et al, 2021). To help resolve these discrepancies, we generated multiple wnt16 loss-of-function alleles using CRISPR/Cas9-based gene editing (Supplemental Fig 2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4B). ( 151 ) Emerging phenomics‐based deletion approaches in mosaic zebrafish (crispants) now present an efficient model for the rapid validation of novel GWAS‐derived genes related to bone disease ( 29,40 ) (Fig. 4B, C, Table 1).…”
Section: Oi and Osteopetrosismentioning
confidence: 99%